Chapter 15 Relational normative thought in Ubuntu and Neo-republicanism - Gädeke, Dorothea (Taylor & Francis, 2019)
Anglo-American and European normative philosophy is essentially individualist in character, while African philosophy is of a collectivist kind. Such general statements are common within the comparative literature on these philosophical traditions. Individualism considers the individual, taken separately, to be of sole and ultimate concern. Thaddeus Metz develops an alternative account based on the fundamental value of harmonious relationships without invoking any perfectionist underpinning. In fact, Metz's approach does not pertain to character. Republicanism arguably formulates the most powerful challenge to liberalism within contemporary Anglo-American and European philosophy. The republican tradition is older than the liberal one, going back to Athens and Rome and the adaptation of ancient political thought in the early modern period. Proponents of the philosophy of Ubuntu consider humane relationships as the core concern of normative thought. Republicanism, by contrast, starts from a negative account of what kind of relationships should be avoided, namely relationships of domination.